Russian Beyond Russia : The Politics of National Identify - Melvin, Neil (London The Royal Institute of International Affaris, 1995)
An examination of the political issues surrounding the fate of ethnic Russians who, since the beginning of 1992, have found themselves living in non-Russian nation-states. Case studies on the development of a national identity within the Russian-speaking communities are provided.
Include Statistical Appendix, Notes and Select Bibliography
Keywords: Soviet Union--Former Soviet republics -- Ethnic relations -- National characteristics, Russian -- Nationalism--Soviet republics